Watch-and-Wait is an Option in Rectal Cancer Patients: From Controversy to Common Clinical Practice. Issue 2 (February 2023) - Grotenhuis, B.A.; Beets, G.L.
Abstract: Overview of the introduction of organ preservation in rectal cancer patients and future challenges.